Spatial Reversal Learning in Chronically Sensitized Rats and in Undrugged Sensitized Rats with Dopamine D2-Like Receptor Agonist Quinpirole - Hatalova, Hana; Radostova, Dominika; Pistikova, Adela; Vales, Karel; Stuchlik, Ales (Frontiers in Behavioral Neuroscience, 2014)
Dopamine plays a role in generating flexible adaptive responses in changing environments. Chronic administration of D2-like agonist quinpirole (QNP) induces behavioral sensitization and stereotypical behaviors reminiscent of obsessive-compulsive disorder (OCD). Some of these symptoms persist even after QNP discontinuation. In QNP- sensitization, perseverative behavior has often been implicated. To test the effect of QNP- sensitization on reversal learning and its association with perseveration we selected an aversively motivated hippocampus-dependent task, active place avoidance on a Carousel. Performance was measured as the number of entrances into a to-be-avoided sector (errors). We tested separately QNP sensitized rats in QNP-drugged and QNP-undrugged state in acquisition and reversal tasks on the Carousel. In acquisition learning there were no significant differences between groups and their respective controls. In reversal, QNP-sensitized drugged rats showed a robust but transient increase in number of errors compared to controls. QNP-sensitized rats in an undrugged state were not overtly different from the control animals but displayed an altered learning manifested by more errors at the beginning compensated by quicker learning in the second session compared to control animals. Importantly performance was not associated with perseveration in neither QNP-sensitized drugged nor QNP-sensitized undrugged animals. The present results show that chronic QNP treatment induces robust reversal learning deficit only when the substance is continuously administered, and suggest that QNP animal model of OCD is also feasible model of cognitive alterations in this disorder.